Promoting Students’ Higher Order Thinking through Flipped Classroom Model in Listening Comprehension Classes - Leni Irianti; R. Bunga Febriani; Lilies Youlia Friatin (VELES Voices of English Language Education Society, 2022)
The teaching of the Listening subject in Higher Education needs to be more innovative and should be conveyed through various classroom activities. The activities in the teaching of listening should be embedded to technology to replace the existing traditional listening classes. Moreover, learners are demanded to improve their higher-order thinking skills to enhance their problem-solving skills through new learning experience. The flipped classroom encourages students to participate more actively in problem solving, either individually or in small groups, encourages students to take ownership of their education, and delivers a novel learning experience. The research examined students' higher-order thinking abilities in experimental and control groups with varying degrees of schooling. The population consists of third-semester students at a private university in Indonesia. The exam was designed to obtain quantitative evidence on how the inverted classroom model increases students' listening capacity and higher-order thinking in English in an EFL environment, and to corroborate the quantitative findings with students' views of the inverted classroom model in listening. The result demonstrates that inverted classes assist students to increase their capacity for higher-order thinking. The flipped classroom model prepared the students outside the class and presented their development in class. They also perceived that this model gives a positive impact on them. This teaching method helped them rewind the material repeatedly and then organize their listening skills in class.